Performance of the Electric Energy Generation in a Photovoltaic System (PV) Based on PELTIER Effect (TEC) inTwo Different Locations, La Mesa and Girardot in the Department of Cundinamarca - Cardona, Juan Felipe
The city of Girardot is located in alto Magdalena region near Magdalena river with an altitude of 289 M.A.S.L. As a consequence, this metropolis has a warm weather around 33 ºC during the entire year, being one of the cities with most sunshine duration per day in middle-Colombia. On the other hand, La Mesa is situated in the Tequendama region at  pproximately 26 ºC of temperature per year and an average altitude of 1200 M.A.S.L.Consequently, this sort of scenario can have significant effects on the production of energy in a photovoltaic system installed in both municipalities. In 2015, the production of more efficient modules was announced by SolarCity, reaching 22,04%. However, Panasonic introduced a similar new solar prototype into the market showing a peak of maximum efficiency of around 22.5%. This data was verified by the national institute of industry science and technology in Japan. It was possible thanks to the new photovoltaic cells withan throughput just over 25.6% that were produced last year.The new photovoltaic unit called Panasonic HIT N330 was made with 96 cells and 330W, which can generate an efficiency of 19.7% per module. Furthermore, the company confirmed that the new photovoltaic unit can provide a peak energy of 27% more than similar standard products with 260 W. The peak of power is the maximum power which can deliver a  photovoltaic cell in a normal condition (radiation of 1000W/m² and temperature of 25 ºC) andit is the parameter standard to classify the power of the modules. A new research published by NATURA energy shows the solution to resolve the low efficiency which is one of the biggest problems with solar energy. This investigation proved that solar panels of silicon developed by kunta yoshikawa in Japan are the most effective panels in the world.Kunta Yoshikawa, who is expert in the photovoltaic area, exhibited the first silicon plaque. This plaque is able to rise up to 26% in efficiency of transformation between solar radiation and electricity. Overall, by using new technologies, the improvement of efficiency has increased considerably about 2.7% (Espectador, 2017).